Skorostnye vozmoznosti prygunov i ich realizacija v razbege - Ogandzanov, A. L.; Cesnokov, N. N.; Ter-Avanesov, E. M. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of the carried out research was the estimation of high-speed capabilities of the best Russian jumpers, degrees of realization of these capabilities in competitive start, and the comparison of parameters of competitive activity with parameters of the best jumpers of the world, also The strongest jumpers of Russia have taken part in the research (23 persons). The backlog in this kind of track and field athletics is connected to lacks of the high-speed preparedness of the majority of our strongest jumpers last years. Thus the special speed-power and technical preparedness of Russian athletes is on the high enough level. The parameter of the speed on the last 5-meter site of the start gain together with the factor of the realization of speed and high-speed parameters of the start can serve as the criteria for an estimation of the technique of the performance of this phase of the jump.